Changes in the Biotransformation of Green Tea Catechins Induced by Different Carbon and Nitrogen Sources in Aspergillus niger RAF106 - Fang, Xiang; Du, Minru; Liu, Tong; Fang, Qian’an; Liao, Zhenlin; Zhong, Qingping; Chen, Jianwen; Meng, Xiaolin; Zhou, Shiyu; Wang, Jie (Frontiers in Microbiology, 2019)
Biotransformation of green tea catechins mediated by microbes and/or enzymes could increase their bioavailability and improve their health benefits, but the regulatory mechanism remains unclear. Here, Aspergillus niger RAF106 isolated from Pu-er tea was proved to be capable of degrading gradually ester-catechins into non-ester catechins with higher bioavailability and gallic acid (GA) in aqueous solution only containing green tea catechins, and the products displayed similar radical-scavenging activity in vitro with the control. Meanwhile, the degradation was mediated by inducible enzymes as the extracellular form, and tannase might be an important enzyme among the extracellular enzymes. Moreover, it was found for the first time that the biotransformation was accelerated significantly by the addition of different nitrogen sources (i.e. yeast extract, peptone, NaNO3 and NH4Cl) and lactose through stimulating the hyphal growth and the tannase activities but was inhibited by glucose effect. Furthermore, nitrogen sources continued to promote the degradation of GA and/or non-ester catechins by up-regulating the transcriptional expression of two dioxygenases and ten monooxygenases. Besides, the addition of different nutrient sources except yeast extract did not alter the radical-scavenging activity of green tea catechins during the whole fermentation. These results provide a global insight into the roles of A. niger RAF106 and different nutrient sources in mediating the biotransformation of green tea catechins and modifying the radical-scavenging activity of biotransformed catechins.